GAMBARAN PERSIAPAN ORANG TUA MEMBAWA ANAK USIA TODDLER KETIKA MELAKUKAN KUNJUNGAN WISATA KE BALI - Swari, Ida Ayu Dwi Nandy; Devi, Ni Luh Putu Shinta; Widyanthari, Desak Made (Coping: Community of Publishing in Nursing, 2021)
Traveling with children especially toddler age has different challenges and problems. Toddlers are fully dependent on their parents for physical safety. Parents have an important role in preventing various problems that can occur in children during a tourist visit. One of them is by making preparations before departure. This study aims to determine the description of the preparation of parents carrying toddler-age children when visiting Bali. This research is a quantitative descriptive study with cross sectional approach. The sample in this study was taken in the area of ??South Kuta, Badung Regency using consecutive sampling techniques to obtain a sample of 100 tourists. Based on the results of the study it was found that the majority of foreign and domestic tourists visiting the South Kuta Area, Badung Regency were 34.5 years old, had a bachelor's degree (62%), worked (76%), were from foreign countries (55%), the frequency of visits >1 time (57%), never get pre-travel advice (76%), bring a child aged 24 months, a female child (52%) and there is an equal proportion between the length of tourist visits <10 days and ?10 days (50%). Some parents who bring toddler-age children visiting Bali are in the poor preparation category (50%), while some other parents (50%) are already in the good preparation category. It is expected that parents want to increase their knowledge about the preparation they have to do when bringing toddler-age children to visit Bali.